“Two Silver Herrings for My Granddaughter”: Central Europe, Poland, and Transnational Affinities. Deborah Levy in Conversation - Robert Kusek; Wojciech Szymański (European Journal of Life Writing)
The piece addresses Deborah Levy’s long-standing dialogue with Central European history and cultural production and the impact that the latter exerted onto her works, including her “living autobiography”. It also  showcases various modes of cultural exchange and transnational affinities between the global West and East in the Cold War period.